Results from the Survey of Antibiotic Resistance (SOAR) 2012-14 in Thailand, India, South Korea and Singapore - D. Torumkuney (2018)
© The Author 2016. Objectives: To provide susceptibility data for community-acquired respiratory tract isolates of Streptococcus pneumoniae, Streptococcus pyogenes, Haemophilus influenzae and Moraxella catarrhalis collected in 2012-14 from four Asian countries. Methods: MICs were determined using Etest®for all antibiotics except erythromycin, which was evaluated by disc diffusion. Susceptibility was assessed using CLSI, EUCAST and pharmacokinetic/pharmacodynamic (PK/PD) breakpoints. For macrolide/clindamycin interpretation, breakpoints were adjusted for incubation in CO2where available. Results: Susceptibility of S. pneumoniae was generally lower in South Korea than in other countries. Penicillin susceptibility assessed using CLSI oral or EUCAST breakpoints ranged from21.2%in South Korea to 63.8%in Singapore. In contrast, susceptibility using CLSI intravenous breakpointswasmuch higher, at 79%in South Korea and ~95%or higher elsewhere. Macrolide susceptibility was ~20% in South Korea and ~50%-60% elsewhere. Among S. pyogenes isolates (India only), erythromycin susceptibility (~20%) was lowest of the antibiotics tested. In H. influenzae antibiotic susceptibility was high except for ampicillin, where susceptibility ranged from 16.7% in South Korea to 91.1% in India. South Korea also had a high percentage (18.1%) of b-lactamase-negative ampicillin-resistant isolates. Amoxicillin/clavulanic acid susceptibility for each pathogen (PK/PD high dose) was between 93% and 100% in all countries except for H. influenzae in South Korea (62.5%). Conclusions: Use of EUCAST versus CLSI breakpoints had profound differences for cefaclor, cefuroxime and ofloxacin, with EUCASTshowing lower susceptibility. Therewas considerable variability in susceptibilityamong countries in the same region. Thus, continued surveillance is necessary to track future changes in antibiotic resistance.